Roemah Entrepreneur is Kind of Social Entrepreneurship - Kusumaniyah, Putri Fajrin; Rudito, Bambang (Journal of Business and Management, 2015)
Abstract.Entrepreneurship is key driver of economic condition of a country. One important role that entrepreneurs play is creating job opportunities. The increased employment level will mitigate or reduce poverty levels and economic disparities and increase the per capita income all of which are indicators of economic development. This final project is to analysis is about social entrepreneurship (a case studty of roemah entrepreneur). The model used assess participation, observation, and interview. This models explain about impact to the member of Roemah Entrepreneur, impact to the surrounding Â community, corporate social responsibility, community development, community empowerment, and social entrepreneurship. To find the data researcher abreasting activity of Roemah Entrepreneur in Kiaracondong, Bandung and interview with staff and member from Roemah Entrepreneur.Keyword : Corporate Social Respontability, Community Development, Social Entrepreneurship